Budidaya ikan nila dengan Sistem BioflokDi Sungai Tello Kota Makassar - Kasnir, Muhammad; zakaria, Junaidin; Syarifuddin (Window of Community Dedication Journal, 2023)
The purpose of this activity is to increase knowledge and skills in the community.especially the tello tilapia group. The expected benefits are the transfer of aquaculture technology with biofloc system that can increase the stocking density of tilapia, the efficiency of feed use and the use of narrow cultivation sites. use of a narrow cultivation location. The implementation method is to provide counseling through increasing the knowledge and skills of the group through counseling and practice. from seed selection, feeding techniques to probiotic making techniques. Results. There was an increase in understanding where the pretest results were conducted on 20 members of the tello tilapia group who were given a questionnaire. members of the tello tilapia group who were given a questionnaire with 10 questions consisting of pretest results, namely 30% had good knowledge, 20% had sufficient knowledge, and 50% had poor knowledge. less knowledge. After being given counseling, there was an increase in knowledge, namely 85% good, 15% sufficient and no longer lacking knowledge about cultivation methods. no longer lacking knowledge about biofloc cultivation methods. The fish farmer group The Tello Tilapia fish farmer group has been able to make Probiotics with cheap ingredients, so that probiotic products can be sold to other community groups with packaging. products can be sold to other community groups with attractive packaging.